Study of Pedestrian Facilities on Jalan Sutan Syahrir and Jalan K.H. Agus Salim, Pontianak, Kalimantan Barat - Alhadad, Syarif Muhammad Rayhan; Mayuni, Siti; Said, Said (Fakultas Teknik Universitas Tanjungpura, 2026)
This study examines the performance of pedestrian facilities along Jalan Sutan Syahrir and Jalan K.H. Agus Salim in Pontianak, Indonesia, two major urban corridors that experience persistent challenges in accessibility, connectivity, and user comfort. The research aims to evaluate sidewalk compliance with prevailing technical standards and to assess user satisfaction. A mixed-method approach was adopted, employing the Guttman Scale to measure conformity with Regulation of the Minister of Public Works No. 03/PRT/M/2014 and Guideline No. 07/P/BM/2023, and the Likert Scale based on interviews with 96 respondents to capture user perceptions. The findings indicate that sidewalks on Jalan Sutan Syahrir demonstrate high compliance in safety, comfort, and aesthetics, yet show deficiencies in accessibility, supporting facilities, and connectivity. Conversely, Jalan K.H. Agus Salim exhibits moderate safety performance but lower ratings in comfort, accessibility, and connectivity. User satisfaction results classify Jalan Sutan Syahrir as generally comfortable, while Jalan K.H. Agus Salim is perceived as uncomfortable. These results highlight the need for targeted improvements to enhance pedestrian mobility.